Tinjauan Sistem Pelayanan Pendaftaran Pasien Rawat Jalan di Rumah Sakit Ernaldi Bahar Provinsi Sumatera Selatan - Party Elliyanti; Popin Septri Badoriasari (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Efforts to improve the quality of outpatient registration services can be carried out properly if they are in accordance with the procedure flow and must meet the average standard of service time at registration. In reality, there are often inhibiting factors that often occur. Find out why outpatient registration services are banned. The research method used is descriptive analysis, namely by observing the overall registration service of the outpatient unit. The population of this study were patients who came to visit the outpatient unit and outpatient registration officers by calculating the average service time provided to patients who came in accordance with established standard procedures. Based on the results that the authors examined, the average time for outpatient registration services obtained a sample of 133 patients, old patients consisted of 120 people and 13 new patients. For old patients, the average service time is about 7 minutes at most and new patients are on average about 11 minutes. The results showed that the outpatient registration service system at Ernaldi Bahar Hospital, South Sumatra Province, can be said to be still not optimal because there are still constraint factors that occur when registering, such as interference with the internet network, and delays in searching for outpatient medical record files because of the printing machine. the tracer is jammed so you have to wait for the SJP/SEP first before the outpatient medical record file can be searched/retrieved to be submitted to the outpatient polyclinic.